The Role and Functions of Teachers in Improving Effective Learning in Classes (International Journal of Food and Nutritional Sciences, 2022)
This study aims to describe the role and function of teachers in enhancing effective learning,inhibiting factors and solutions to teacher barriers in carrying out the roles and functions of teachers atthe Schoolsand Colleges. This study used a descriptive qualitative approach with a case study design.Data collection techniques used are observation, interview, and documentation. Which is mentionedthat the teacher is a professional educator with the main task of educating, teaching, guiding,directing, training, evaluating, and evaluating students in early childhood education informaleducation, basic education, and secondary education.